2017
DOI: 10.1080/07388551.2017.1355293
|View full text |Cite
|
Sign up to set email alerts
|

An overview on biodegradation of polystyrene and modified polystyrene: the microbial approach

Abstract: Polystyrene is a widely used plastic in many aspects of human life and in industries due to its useful characteristics of low cost, light weight, ease of manufacture, versatility, thermal efficiency, durability, and moisture resistance. However, polystyrene is very stable and extremely hard to degrade in the environment after disposal. Polystyrene can be used as a carbon source for microorganisms similar to many other hydrocarbons. The ability of microorganisms to use polystyrene as a carbon source has been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
185
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(193 citation statements)
references
References 54 publications
2
185
0
6
Order By: Relevance
“…Danso et al [22] retrieved two metagenomic PET hydrolase sequences from hmm probabilistic models that were functionally active in polycaprolactone and PET hydrolysis, supporting the approach of undermining the metabolic potential in environmental microbiomes to degrade priority pollutants. Several studies suggest that the degradation of polystyrene by bacteria occurs due to individual oxidizing units of styrene, through monooxygenase activities [61]. Six oxygenase (StyA) candidate's genes were found (Table 4).…”
Section: Microbial Genes and Enzymes Involved In The Degradation Of Imentioning
confidence: 99%
“…Danso et al [22] retrieved two metagenomic PET hydrolase sequences from hmm probabilistic models that were functionally active in polycaprolactone and PET hydrolysis, supporting the approach of undermining the metabolic potential in environmental microbiomes to degrade priority pollutants. Several studies suggest that the degradation of polystyrene by bacteria occurs due to individual oxidizing units of styrene, through monooxygenase activities [61]. Six oxygenase (StyA) candidate's genes were found (Table 4).…”
Section: Microbial Genes and Enzymes Involved In The Degradation Of Imentioning
confidence: 99%
“…In recent years, a number of studies have reported that several microorganisms and enzymes are capable of degrading synthetic plastics. Although numerous reviews and viewpoints on the topic of biodegradation of plastic have been published, they have mainly focused on the biodegradation of a single kind of plastic, such as PE (Restrepo-Flórez et al, 2014), PS (Ho et al, 2018), PP (Arutchelvi et al, 2008), PUR (Cregut et al, 2013;Peng et al, 2018;Magnin et al, 2019c), and PET (Wei and Zimmermann, 2017a;Kawai et al, 2019;Taniguchi et al, 2019). A comprehensive review into biodegradation of all main kinds of plastic is necessary (Wei and Zimmermann, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…PS is a sturdy thermoplastic commonly used in short-lifetime items that contribute broadly to the mass of poorly controlled polymers [53]. Various forms of PS such as general purpose (GPPS)/oriented polystyrene (OPS), polystyrene foam, and expanded polystyrene (EPS) foam are available for different commercial leading to a broad solid waste composition.…”
Section: Polystyrenementioning
confidence: 99%